2022
DOI: 10.3390/jcm11206221
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Treatment with Cognitive Behavioral Therapeutic Intervention Plus Bladder Treatment Is More Effective than Monotherapy for Patients with Interstitial Cystitis/Bladder Pain Syndrome—A Randomized Clinical Trial

Abstract: (1) Background: Introduction: Interstitial cystitis/bladder pain syndrome (IC/BPS) not only induces physiological damage but also greatly affects psychological stress. Multidisciplinary therapy has been recommended for IC/BPS treatment, but clinical trial data of combined bladder therapy and cognitive behavioral therapy (CBT) are lacking. This study evaluated CBT efficacy in patients with IC/BPS. (2) Methods: Patients with IC/BPS were randomized to the bladder monotherapy (BT) or combined CBT (CBT) group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…118,119 According to these studies, LESW and PTNS/TENS could improve bladder symptoms in most NHIC patients, [108][109][110]113,116,117 whereas education, CBT, and lifestyle modification might assist patients in coping with their symptoms regardless of their bladder condition. 96,98,100 PFMP may benefit from a combination of pelvic floor muscle treatment in patients who have pelvic floor myofascial pain. 119 Most experimental studies have indicated that the trigger points of PFMP contribute to peripheral and central sensitizations because they can affect peripheral nociceptors, spinal dorsal horn neurons, and brainstem.…”
Section: Current Treatment Modalities and Constructing Diagnostic And...mentioning
confidence: 99%
See 4 more Smart Citations
“…118,119 According to these studies, LESW and PTNS/TENS could improve bladder symptoms in most NHIC patients, [108][109][110]113,116,117 whereas education, CBT, and lifestyle modification might assist patients in coping with their symptoms regardless of their bladder condition. 96,98,100 PFMP may benefit from a combination of pelvic floor muscle treatment in patients who have pelvic floor myofascial pain. 119 Most experimental studies have indicated that the trigger points of PFMP contribute to peripheral and central sensitizations because they can affect peripheral nociceptors, spinal dorsal horn neurons, and brainstem.…”
Section: Current Treatment Modalities and Constructing Diagnostic And...mentioning
confidence: 99%
“…14 Certainly, psychiatric treatments and stress therapy might be enrolled in both HIC and NHIC patients. 96,98,121 Most studies on NHIC have focused on monotherapy targeting the urinary bladder, with only partial evidence of durable effectiveness. Figure 1…”
Section: Current Treatment Modalities and Constructing Diagnostic And...mentioning
confidence: 99%
See 3 more Smart Citations